Structural and mechanical properties of staghorn coral (Acropora cervicornis) CaCO3 aragonite skeletons, cleaned by chemical bleaching and biological processes. (16th November 2020) - Omer, Mahmoud; Carrasco-Pena, Alejandro; Orlovskaya, Nina; Collins, Boyce E.; Yarmolenko, Sergey N.; Sankar, Jagannathan; Subhash, Ghatu; Gilliam, David S.; Fauth, John E.
ABSTRACT : Coral reefs provide habitat for most oceanic life forms, however, they are declining worldwide due to pollution, increased ocean temperature, diseases and other factors. In this paper, structural and mechanical properties of endangered coral ( Acropora cervicornis ) skeletons cleaned by chemical bleaching and biological processes were studied. The structure of CaCO3 aragonite skeleton is porous and very complex and affects the deformation behaviour of coral skeletons. The average compressive strength was equal to 9.5 ± 2.3 MPa and 14.5 ± 6.4 MPa, while Vickers hardness was measured to be equal to 3.67 ± 0.33 GPa and 3.65 ± 0.24 GPa for the chemically bleached and biologically cleaned skeletons, respectively, thus showing similar values regardless of the cleaning techniques. The results are important for understanding the fundamental relationship between the coral skeleton's microstructure and mechanical behaviour.